2017
DOI: 10.1038/s41598-017-03283-x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of retinal pigment epithelial cell properties under the exposure of cotinine

Abstract: Cigarette smoking is a major risk factor for age-related macular degeneration (AMD), in which progressive retinal pigment epithelial (RPE) cell degeneration is a major pathological change. Nicotine is a major biologically active component in cigarette smoke. It is continuously catabolized into cotinine, which has longer half-life and higher concentration in tissue cells and fluids. Here we hypothesized that continuous exposure of cotinine has more potent effects on human RPE cell properties than nicotine. Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Smoking is not only associated with developing CSC, but poor visual prognosis and longer treatment needed in CSC patients 41 . Cotinine, the major nicotine metabolite, reduces RPE cell repair, wound healing ability and phagocytotic activity in vitro 42 . Fujihara et al reported that chronic cigarette smoke develops evidence of oxidative damage with ultrastructural degeneration to the RPE and Bruch's membrane, and RPE cell apoptosis 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is not only associated with developing CSC, but poor visual prognosis and longer treatment needed in CSC patients 41 . Cotinine, the major nicotine metabolite, reduces RPE cell repair, wound healing ability and phagocytotic activity in vitro 42 . Fujihara et al reported that chronic cigarette smoke develops evidence of oxidative damage with ultrastructural degeneration to the RPE and Bruch's membrane, and RPE cell apoptosis 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Human ocular cell lines, including retinal pigment epithelial (RPE) cells ARPE-19 (catalogue number: CRL-2302, American Type Culture Collection (ATCC), Manassas, VA) [11,12], lens epithelial cells B3 (catalogue number: CRL-11421, ATCC) [13], primary trabecular meshwork (TM) cells [14], and retinoblastoma cells Y79 (catalogue number: HTB-18, ATCC) [15], have been previously established. We also collected human mesenchymal stem cells (MSCs) from different sources, including bone marrow-derived MSCs (BM-MSCs; catalogue number: 7500; ScienceCell Research Laboratories, Carlsbad, CA) [16], adipose-derived stem cells (ASCs) [17], and periodontal ligament-derived stem cells (PDLSCs) [18,19].…”
Section: Human Cell Lines and Mouse Tissuesmentioning
confidence: 99%
“…Smoking is not only associated with developing CSC, but poor visual prognosis and longer treatment needed in CSC patients [33]. Cotinine, the major nicotine metabolite, reduces RPE cell repair, wound healing ability and phagocytotic activity in vitro [34]. Fujihara et al reported that chronic cigarette smoke develops evidence of oxidative damage with ultrastructural degeneration to the RPE and Bruch membrane, and RPE cell apoptosis [35].…”
Section: Discussionmentioning
confidence: 99%